FAKTOR-FAKTOR YANG MEMPENGARUHI IBU DALAM PEMBERIAN MAKANAN PENDAMPING ASI DINI DI KELURAHAN BANDAR SELAMAT KECAMATAN MEDAN TEMBUNG TAHUN 2015 - Novi Agustina Batubara (Jurnal Ilmiah Kebidanan Imelda, 2016)
Complemented food is the food given besides breastmilk to fill the nutrition need. Giving complemented food too early is risky to the babies since it can cause digestive infection which lead to intestine invaginasi/ intususepsi. Therefore the complemented food should be given after the age of six months. The benefits are giving protection from infection and obesity in the future. This study is aimed to define the factors effected in giving early complemented food in Kelurahan Bandar Selamat Kecamatan Medan Tembung. This is an analityc study with cross-sectional design. The population is all the mothers who have 6 – 12 months babies. The samples are 116 cases using Total Sampling. The collecting data method included primary and secondary data. The data were analyzed with univariat, bivariat and multivariat. The results of the study show there is significant relation between age and early giving complemented food with p-value = 0.000; there is significant relation between parity and early giving complemented food with p-value = 0,004; there is significant relation between educational level and early giving complemented food with p-value = 0,001; there is significant relation between occupation and early giving complemented food with p-value = 0,000; there is significant relation between knowledge and early giving complemented food with p-value = 0,000; there is significant relation between income and early giving complemented food with p-value = 0,000; there is significant relation between the support from health workers and early giving complemented food with p-value = 0,000; there is significant relation between the support from family and early giving complemented food with p-value = 0,000; the most dominant factor is knowledge with p-value 0,005 and exp (B) = 4,531. It is suggested to the health workers to give explanation about the correct time in giving complemented food and improve the exclusive breastfeeding.